Providing Health Services For The Public in Hospitals Based on A Justice Theory Perspective - Nainggolan, Ibrahim; Koto, Ismail; Koto, Zulkarnain (Jurnal Hukum Replik, 2024)
In the rapidly evolving field of medicine, the role of hospitals is crucial in promoting community health. The progress and setbacks of hospitals hinge significantly on the success of the individuals working within them, including doctors, nurses, and other staff. Aristotle's theory of justice, asserting that justice is not only a general virtue but also a specific moral virtue related to human conduct in particular fields, becomes pertinent in the healthcare domain. This theory revolves around establishing positive relationships among individuals and maintaining a balance between two parties. The measure of this balance involves both numerical and proportional equality, as Aristotle conceives justice in terms of equality. Numerical equality dictates that every individual is regarded as equal in a unified unit, such as the equality of all individuals before the law. Proportional equality, on the other hand, involves giving each person what is rightfully theirs based on their abilities and achievements. The application of Aristotle's theory of justice in the healthcare services for the Indonesian populace is evident in the various government-initiated healthcare assurance programs like the Workers' Social Security, Askes, and the Social Security Administration Body. This endeavor aims to ensure that the entire spectrum of society receives equal healthcare services, as it is considered the inherent rights of citizens and the community.